Entrepreneurship-based Financing Strategy Towards Pesantren Independence - Yulia Kuraesin Ila Rohima; Mohammad Sabarudin; Rahmat; Sri Wulan; Badrudin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research analyzes entrepreneurship-based financing strategies at the Pesantren Daarut Tauhiid (DT), Bandung. This research uses a qualitative approach with a case study method involving in-depth interviews and participant observation. The data analysis techniques include data reduction, data presentation, and conclusion. Data obtained from interviews and observations were analyzed inductively, with steps in the form of coding, grouping themes, and interpretation to gain an in-depth understanding of the phenomenon under study. The results of the research show that the entrepreneurial strategy implemented includes the development of business units such as the business units at the Pesantren Daarut Tauhiid, namely Vehicle Rental, Service Bureau, Tour and Travel, and Event Organizer. Apart from that, there are also Sharia Financial Services, namely BMT Daarut Tauhiid and PT. BPRS Daarut Tauhiid has succeeded in increasing the independence of Pesantren Daarut Tauhiids. The Pesantren Daarut Tauhiid applies a management model focusing on productive waqf, providing broad benefits to the congregation and society. Not only financially but also non-commercially. However, Pesantren Daarut Tauhiids still face challenges in human resource management and capacity development. This research recommends increasing entrepreneurship training for students and Pesantren Daarut Tauhiid managers and expanding business diversification to improve the financial stability of Pesantren Daarut Tauhiids.